Kearifan lokal suku Madura dalam menjaga tradisi nilai sosial dan identitas budaya modern - Lestari, Dwi Indah; Kurnia, Heri; Hendri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
The Madura tribe is one of the major ethnicities in Indonesia that has a rich socio-cultural heritage with its own characteristics, ranging from the tradition of cow karapan and sonok cows, to strong values of solidarity and religiosity. However, the development of globalization poses challenges to the preservation of this culture, such as shifting the meaning of traditions, weakening social solidarity, and reduced use of the Madurese language among the younger generation. This research aims to analyze the socio-social and cultural values of the Madura people and examine how they adapt in the era of globalization. This research uses a literature study method by examining various sources in the form of books, articles, and scientific journals that are relevant about the socio-culture of the Madura people. The analysis is carried out by emphasizing aspects of social characteristics, cultural traditions, and challenges faced in the modern era. The results of the study show that although Madura culture faces serious threats due to modernization and negative stereotypes, noble values such as self-respect, mutual cooperation, and religiosity remain a strong foundation. Cultural preservation needs to be directed at innovation and digitalization to remain relevant in the future.